STEP AEROBICS AT THE PHYSICAL EDUCATION LESSONS - Zaikin, Andrey; Glavatskaya, Elena (Вісник Кам’янець-Подільського національного університету імені Івана Огієнка. Фізичне виховання, спорт і здоров’я людини, 2013)
An analysis of the literature, which provides an explanation of the origin and development of step aerobics is done in the article. The positive impact of step aerobics on the bodies of school children is substantiated, methodical instructions for teachers of Physical Education during step aerobics lessons, are defined.